2022
DOI: 10.3390/jcm11113160
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Hematopoiesis and the Risk of Hematologic Malignancies after Curative Therapies for Sickle Cell Disease

Abstract: Sickle cell disease (SCD) is associated with severe morbidity and early mortality. Two large population studies found an increased risk for leukemia in individuals with SCD. Notably, while the relative risk of leukemia development is high, the absolute risk is low in individuals with SCD who do not receive cell-based therapies. However, the risk of leukemia in SCD is high after graft rejection and with gene therapy. Clonal hematopoiesis (CH) is a well-recognized premalignant condition in the general population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…28 Recent reports about a higher incidence of clonal hematopoiesis in SCD and secondary hematological malignancies after graft failure or in case of poor donor chimerism in transplanted SCD patients have raised concerns about the safety of nonmyeloablative conditioning regimens aiming for stable mixed chimerism. 13,29,30 In one study, three of 19 patients developed leukemia after rejection out of a total cohort of 76 transplanted patients with SCD. 12 Two patients had TP53 mutation at diagnosis of leukemia, which turned out to be already present before the transplant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…28 Recent reports about a higher incidence of clonal hematopoiesis in SCD and secondary hematological malignancies after graft failure or in case of poor donor chimerism in transplanted SCD patients have raised concerns about the safety of nonmyeloablative conditioning regimens aiming for stable mixed chimerism. 13,29,30 In one study, three of 19 patients developed leukemia after rejection out of a total cohort of 76 transplanted patients with SCD. 12 Two patients had TP53 mutation at diagnosis of leukemia, which turned out to be already present before the transplant.…”
Section: Discussionmentioning
confidence: 99%
“…13 Additionally, it is postulated that the proliferative stress of regenerative hematopoiesis after graft rejection, or autologous repopulation after gene therapy following exposure to toxic chemo-or radiotherapy may drive clonal expansion of pre-existing mutations. 13 Next to graft failure, mixed chimerism has also been reported as a risk factor for secondary hematological malignancies in transplant recipients with SCD. 29 In the series described by Lawal et al, 29 donor myeloid chimerism in transplant recipients developing myeloid malignancies was <40% in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite limitations coming from the retrospective nature of our study involving missing data and biases related to cases reported over an extended period, our review of the literature tend to suggest that chronic hemolysis, increased iron levels, and increased bone marrow turnover, which form the pathophysiologic mechanisms of the clinical manifestations of SCD are mainly responsible for a situation in which cells are undergoing constant hematopoietic hyperplasia, leading to the increased risk of acute leukemia by inducing genomic damage and somatic mutations [ 77 ]. The effects of SCD on progenitor cells have not been fully determined [ 78 ].…”
Section: Discussionmentioning
confidence: 99%